2020
DOI: 10.1108/wjstsd-08-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–temporal dynamics of rainfall erosivity in the state of Espírito Santo (Brazil) from remote sensing data

Abstract: PurposeThe most common methodology to estimate erosivity is using rainfall data obtained from rain monitoring stations. However, the quality of this estimation may be compromised due to low density, operational problems and maintenance cost of rainfall monitoring stations, common problem encountered in developing countries such as Brazil. The objective of this study was to evaluate the applicability of pluviometric data obtained by TRMM satellite images for the spatiotemporal characterization of erosivity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This is in accordance with the results of Oğuz (2019) 2009) may be due to an embedded underestimation of the kinetic energy due to RUSLE methodology. Although there was still no test of the effectiveness of the modified Fournier index -until this study-, the MF method has been used for Brazilian conditions as a rainfall erosivity estimator in several parts of the country, as the states of Santa Catarina (Back et al, 2018), Espírito Santo (Moreira et al, 2020), Tocantins (Avanzi et al, 2019), Mato Grosso (Di Raimo et al, 2018), São Paulo (Lombardi Neto, 1977, and Amazonas (Silva et al, 2020), along with large areas for regional studies (Mello et al, 2013(Mello et al, , 2015Oliveira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with the results of Oğuz (2019) 2009) may be due to an embedded underestimation of the kinetic energy due to RUSLE methodology. Although there was still no test of the effectiveness of the modified Fournier index -until this study-, the MF method has been used for Brazilian conditions as a rainfall erosivity estimator in several parts of the country, as the states of Santa Catarina (Back et al, 2018), Espírito Santo (Moreira et al, 2020), Tocantins (Avanzi et al, 2019), Mato Grosso (Di Raimo et al, 2018), São Paulo (Lombardi Neto, 1977, and Amazonas (Silva et al, 2020), along with large areas for regional studies (Mello et al, 2013(Mello et al, , 2015Oliveira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Other methodologies, such as rainfall disaggregation (Silveira, 2000) -considering annual or monthly totals for hourly or shorter periods-, or techniques based on orbital remote sensing to estimate rainfall depth (Duarte and Silva Filho, 2019;Li et al, 2020;Moreira et al, 2020), can be used at locations with low density of rain gauge data points. Rainfall erosivity mapping for Africa utilizing Tropical Rainfall Measurement Mission (TRMM), based on TMPA 3B43 satellite data (precipitation data) coupled with the modified Fournier index, proved to be a reliable methodology (Vrieling et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although other input data were given at high spatial resolutions ranging from 90 to 250 m (e.g., elevation, land cover, soil, and vegetation), rainfall data was used at a lower spatial resolution. The Tropical Rainfall Measuring Mission (TRMM) dataset was used as the source of rainfall data in the estimation of rainfall erosivity (Li et al, 2020;Moreira et al, 2020;Vrieling et al, 2010) and soil loss mapping (Dutta et al, 2015;Haregeweyn et al, 2017). However, the coarse spatial resolution of TRMM (0.25°) may fail to capture the detailed precipitation spatial patterns, particularly on the basin and local scales.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the López López et al (2018) study showed that discharge model estimates closely matched observations when the model was forced with the downscaled precipitation. In contrast, soil erosion studies focused on the impact of spatiotemporal precipitation changes on rainfall erosivity (e.g., Moreira et al, 2020) or improving rainfall erosivity by integrating TRMM and rain gauge data (e.g., Teng et al, 2017). Therefore, we attempted to investigate the impact of downscaling precipitation on rainfall erosivity and the resulting soil loss rate.…”
Section: Introductionmentioning
confidence: 99%